Liquid–liquid phase separation in particles containing organics mixed with ammonium sulfate, ammonium bisulfate, ammonium nitrate or sodium chloride - You, Y.; Renbaum-Wolff, L.; Bertram, A. K. (Atmospheric chemistry and physics, 2013)
As the relative humidity varies from high to low values in the atmosphere, particles containing organic species and inorganic salts may undergo liquid–liquid phase separation. The majority of the laboratory work on this subject has used ammonium sulfate as the inorganic salt. In the following we studied liquid–liquid phase separation in particles containing organics mixed with the following salts: ammonium sulfate, ammonium bisulfate, ammonium nitrate and sodium chloride. In each experiment one organic was mixed with one inorganic salt and the liquid–liquid phase separation relative humidity (SRH) was determined. Since we studied 23 different organics mixed with four different salts, a total of 92 different particle types were investigated. Out of the 92 types, 49 underwent liquid–liquid phase separation. For all the inorganic salts, liquid–liquid phase separation was never observed when the oxygen-to-carbon elemental ratio (O : C) 0.8 and was always observed for O : C < 0.5. For 0.5 O : C < 0.8, the results depended on the salt type. Out of the 23 organic species investigated, the SRH of 20 organics followed the trend: (NH4)2SO4 NH4HSO4 NaCl NH4NO3. This trend is consistent with previous salting out studies and the Hofmeister series. Based on the range of O : C values found in the atmosphere and the current results, liquid–liquid phase separation is likely a frequent occurrence in both marine and non-marine environments.